Vulnerability Analysis of Sea Level Rise In The Southern Coast of Bawean Island - Zainul Hidayah; Agus Romadhon; Yudha Witjarnoko (Universitas Gadjah Mada, 2018)
Bawean island is one of numerous small islands in East Java. This island is famous for its natural resources and high level of environmental services. However in the last few years, effects of sea level rises on the island have been reported. Objective of this research was to identify and determine parameters that have significant impact on the vulnerability of the island due to sea level rise events. This research was conducted from July untill September 2017. The method used for this study was a combination of spatial analysis using remote sensing and Geographical Information System (GIS), field survey and interviews with local people. Vulnerability assesment was conducted for three parameters, namely Exposure, Sensitivity and Adaptive Capacity. The results showed that the vulnerability index in the southern part of the island is 3.381. It can be classified as low vulnerability.